Prediksi Jumlah Zakat Melalui Angka Kemiskinan di Kota Padang dengan Menggunakan Metode Graybill - Dwi Wahyu Wigati; Helma Helma (Journal of Mathematics UNP, 2020)
Abstract–If want the poverty rate in the Padang City to drop by a certain amount, then the amount of zakat must be estimated. The research was conducted to obtain predictions of reducing poverty through the amount of zakat with inverse regression using the Graybill method. The data of this research is secondary data. Data obtained through the Padang City BAZNAS about the amount of zakat collected and through the BPS website Padang City about the percentage of poor people of Padang City in 2005-2017. The results of research obtained a prediction model of the amount of zakat that must be provided ( ) in Padang for poverty rates .Keywords–Poverty, Zakat, Inverse Regression, Graybill Method.